Governance and Optimization of Non-Tax State Revenues from the Utilization of Fishery Resources in Indonesia - Zulfadli Ahmad Sary; Igka Ulupui; Indra Pahala (Journal of Social Research, 2025)
Indonesia’s fishery resources hold significant yet underutilized potential for Non-Tax State Revenue (PNBP), with realization rates stagnating at 73.3% due to governance inefficiencies, weak coordination, and outdated policies. This study analyzes PNBP governance challenges, explores optimization strategies (e.g., digitization, PIT policy), and evaluates their potential to enhance revenue while ensuring sustainability. A qualitative case-study approach was employed, using in-depth interviews, document analysis, and observations at Indonesia’s Ministry of Maritime Affairs and Fisheries, framed by good governance and fiscal theories (Miles & Huberman, 2014). Key barriers include regulatory mismatches, multispecies management complexities, and low stakeholder engagement. The PIT policy and e-PIT digitization demonstrate promise in boosting revenue (e.g., via quota systems) but require stronger enforcement and cross-sector synergy. The study contributes to fiscal decentralization theory and offers practical solutions (e.g., tariff adjustments, transparency mechanisms). It calls for future quantitative-spatial research to address data gaps and integrate socio-environmental dimensions.